2(u-3)=3u+5-2(-4u-2)

Simple and best practice solution for 2(u-3)=3u+5-2(-4u-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(u-3)=3u+5-2(-4u-2) equation:



2(u-3)=3u+5-2(-4u-2)
We move all terms to the left:
2(u-3)-(3u+5-2(-4u-2))=0
We multiply parentheses
2u-(3u+5-2(-4u-2))-6=0
We calculate terms in parentheses: -(3u+5-2(-4u-2)), so:
3u+5-2(-4u-2)
determiningTheFunctionDomain 3u-2(-4u-2)+5
We multiply parentheses
3u+8u+4+5
We add all the numbers together, and all the variables
11u+9
Back to the equation:
-(11u+9)
We get rid of parentheses
2u-11u-9-6=0
We add all the numbers together, and all the variables
-9u-15=0
We move all terms containing u to the left, all other terms to the right
-9u=15
u=15/-9
u=-1+2/3

See similar equations:

| 5x-17=3×+1 | | 4z=–3+5z | | 3 16×b=−9 8b= | | 299,792,458=5.915*10^12/t | | -3x+150=x | | 18.5+.15x=18+0.25x | | 17−x=13 | | 7(w+8)=2w+36 | | 4r-8=5r+22= | | t7=6 | | -3x-4x=-12x7 | | 3x-(11x+14)+10=x+ | | -7(x+2)=x-8+2(5x+1) | | -x/4-x/3=-7 | | 4x-10=11-2x | | -4x=10x+30 | | 3w-9=-22 | | 1.50x+2226-6x=882 | | 1.1+0.1x=0.6x-5.4 | | 7x+5x+3+14x=180 | | 3x-150+5x=4730 | | 100=26x-4 | | n/5=1.7 | | 180=26x-4+100 | | 5x+3-7x-14x=180 | | 1/3(12f-3)=2f-1 | | 3y=6(-5)+15 | | 180=x+136+130 | | 5-w/2=12 | | z-12+25=35-10 | | -6x+-3=12 | | 8/z=40 |

Equations solver categories